113k views
20 votes
Integrate y = (2x + 2)^5 with respect to x

User Ksming
by
5.5k points

1 Answer

9 votes

∫ (2x + 2)⁵ dx

Substitute u = 2x + 2, so that du = 2 dx. Then

∫ (2x + 2)⁵ dx = ∫ u ⁵ (du/2) = 1/2 ∫ u ⁵ du

Use the power rule:

1/2 ∫ u ⁵ du = 1/2 (1/6 u ⁶) + C = 1/12 u ⁶ + C

Replace u to get the antiderivative back in terms of x :

∫ (2x + 2)⁵ dx = 1/12 (2x + 2)⁶ + C

and the result can be simplified a bit as

(2x + 2)⁶ = 2⁶ (x + 1)⁶

→ ∫ (2x + 2)⁵ dx = 2⁴/3 (x + 1)⁶ + C = 16/3 (x + 1)⁶ + C

User Gabbar
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.